Correlative 99m Tc-labeled tropane derivative single photon emission computer tomography and clinical assessment in the staging of parkinson disease - Ajit Shinto; Joppy Antony; Koramadai Kamaleshwaran; Krishnan Vijayan; Arul Selvan; Aruna Korde; Mythili Kameshwaran; Grace Samuel (World Journal of Nuclear Medicine)
Parkinson′s disease (PD) is a progressive neurodegenerative disorder characterized by a selective loss of dopamine in the striatum. Problems remain in the accurate diagnosis of PD. The diagnosis of idiopathic PD is based on the interpretation of clinical signs and symptoms could be incorrect at the time of initial presentation. In vivo imaging of the dopaminergic system has the potential to improve the diagnosis of PD in its early stages. The imaging of dopamine transporter (DAT) with 99m Tc-labeled tropane derivative (TRODAT-1) single photon emission computer tomography/computer tomography (SPECT/CT) has been proposed to be a valuable and feasible means of assessment of the integrity of dopamine neurons. The purpose of this study was to investigate the potential usefulness of 99m Tc-TRODAT-1 imaging in the evaluation of patients with PD and classify into different stages of the disease. SPECT imaging with 99m Tc-TRODAT-1 was conducted in 16 consecutive PD patients (9 men; 7 women) and in 6 age matched healthy volunteers (4 men; 2 women). The images were obtained 3 h after the intra-venous injection of the tracer. Specific uptake in the striatum and its sub-regions, including the putamen and caudate nucleus was calculated and the ratios of specific striatal binding to nonspecific occipital binding were calculated. ANOVA with Dunnett C post-hoc analysis was conducted using SPSS 20. A stepwise reduction in specific striatal uptake of 99m Tc-TRODAT-1 with increasing disease severity between healthy control versus Stage I versus Stage II versus Stage III was found in PD patients (i.e., 3.77 vs. 2.56 vs. 1.57 vs. 0.63, P < 0.05). The changes were magnified by measurement of specific putaminal uptake (1.43 vs. 0.79 vs. 0.54 vs. 0.19, P < 0.05) and specific caudate uptake (1.90 vs. 1.47 vs. 0.73 vs. 0.27, P < 0.05). No remarkable adverse reactions were found in either healthy volunteers or PD patients during or after imaging. 99m Tc-TRODAT-1 is accurate and widely available for the assessment of DAT activity, which might shed light on the integrity of the presynaptic nigrostriatal function. Our preliminary study results confirm the potential of using 99m Tc-TRODAT-1 for DAT measurement, which is clinically important for the staging of PD.